Answer
$5C-2B=\left[ \begin{matrix}
-5 & -7 \\
-1 & 9 \\
\end{matrix} \right]$
Work Step by Step
$\begin{align}
& 5C-2B=5\left[ \begin{matrix}
1 & -1 \\
-1 & 1 \\
\end{matrix} \right]-2\left[ \begin{matrix}
5 & 1 \\
-2 & -2 \\
\end{matrix} \right] \\
& =\left[ \begin{matrix}
5\times 1 & 5\times -1 \\
5\times -1 & 5\times 1 \\
\end{matrix} \right]-\left[ \begin{matrix}
2\times 5 & 2\times 1 \\
2\times \left( -2 \right) & 2\times \left( -2 \right) \\
\end{matrix} \right] \\
& =\left[ \begin{matrix}
5 & -5 \\
-5 & 5 \\
\end{matrix} \right]-\left[ \begin{matrix}
10 & 2 \\
-4 & -4 \\
\end{matrix} \right] \\
& =\left[ \begin{matrix}
5-10 & -5-2 \\
-5+4 & 5+4 \\
\end{matrix} \right] \\
& =\left[ \begin{matrix}
-5 & -7 \\
-1 & 9 \\
\end{matrix} \right]
\end{align}$